Pengaruh Ekstrak Bawang Merah (Allium cepa L.) terhadap Gambaran Leukosit Tikus Wistar yang Diinfeksi Staphylococcus aureus - Munawaroh, Muhammad; Angkasa, Winoto; Santosa, Christin Marganingsih; Kholik, Kholik; Rosyadi, Imron (Jurnal Sain Veteriner, 2025)
Shallot (Allium cepa L) has been used emperically to treat wounds, bloat, common cold and is known to boost immunity. Shallots have a variety of useful compounds such as flavonoids, antioxidants, quercetin, saponins and many other compounds. These compounds have been known to have antibacterials, antihistamines, and immunomodulators activities. This study aimed to examine the  potential of shallot extract in wounded rats that are infected with Staphylococcus aureus.Fifteen female Wistar rat were divided into 5 treatment groups: 40% shallot extract, 80% shallot extract, 10% povidone iodine, positive control and negative control. The rats were wounded by making an incision on the back then the shallot extract was administered topically once a day for 21 days. Blood samples were taken on days 0 and 21 then the total number of leukocytes and its differentials     (neutrophils, lymphocytes, monocytes, eosinophils and basophils) were calculated. The data were then processed using one-way ANOVA test with 95% significance value.The result showed a significant increase (p<0,05) on the total number of leukocyte (10,37 ± 1,09 103/µl), neutrophils (4,98 ± 0,30 103/µl), lymphocytes  (8,76 ± 0,04 103/µl) and monocytes (0,74 ± 0,02 103/µl) on the group treated with 40% shallot extract. While on the group treated with 80% shallot extract there was a significant increase (p<0,005) on the total number of leukocytes (10,40 ± 0,43 103/µl), lymphocytes (7,67 ± 0,19 103/µl), and monocytes (0,64 ± 0,01 103/µl). This study concluded that shallot extract is able to improve the immune system.